Cervical cancer and pregnancy - Lagrutta, J. (2015)
The authors present their experience in the Instituto de Maternidad de la Plata, Argentina, from two aspects: 1) The antecedent of pregnancy in 185 cases of carcinoma of the cervix; they found that 36 of them had a pregnancy in a lapse of two years to the time of diagnosis. 2) In the examination of 640 pregnancies with some type of cervical pathology, 9 cases of carcinoma were found; this means an incidence of 1.4%. Some therapeutic attitudes are also presented.